Biological Method with Pseudomonas Putida for Chromium Vi Reduction in Chromium Plating Process Wastewater - Elmer Benites-Alfaro; Danny Lizarzaburu Aguinaga; Carlos Cabrera Carranza; Jorge Jave Nakayo; Guido Rene Suca-Apaza; Jose Freddy Atuncar Yrribari; Jorge Lopez Bulnes; Felipa Munoz-Ccuro (Chemical Engineering Transactions)
The issue surrounding wastewater from the industrial chrome plating process is highly relevant due to its negative environmental and public health impacts. In the chrome plating of metals and other substrates, toxic chemicals are used, including chromic acid and heavy metals that contaminate the water used in the process, generating contaminated effluents that must be treated before disposal into receiving bodies. One of the substances presents in these effluents is the highly hazardous and known carcinogen hexavalent chromium, which requires the development of treatment technologies to reduce or eliminate the effluent. The objective of the research was to reduce hexavalent chromium in industrial chrome plating water samples (M1, M2, and M3) using a biological method using the bacterium’s bacteriums. Three different concentrations of bacterium were tested in volume percentages (30, 40, and 60 %) for 21 days, with the process being monitored every 7 days. At the end of the trial, the concentration of hexavalent chromium (Cr VI) was reduced by approximately 76 %. It is concluded that this methodology is efficient in the non-toxic reduction of Cr VI, economical compared to physical and chemical methods in the long term, and sustainable as it does not generate toxic waste; but above all, it is a promising and very environmentally friendly methodology.